PELATIHAN KETERAMPILAN MENJAHIT DIVERSIFIKASI PRODUK BATIK PADA KELOMPOK BATIK KARISMA AGUNG DESA SUMBERAGUNG MALANG - Annisau Nafiah; Hapsari Kusumawardani; Nurul Aini; Agus Hery Supadmi Irianti (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract In order to turn batik into apparel, the Karisma batik group really needs training on how to sew clothes. This sewing training is very important to equip human resources to be skilled in making clothes so that batik, which was previously in the form of sheets of clothing material, can become ready-made and ready-to-wear clothes. The limited human resources we have to explore batik products inspired us. The PKM UM TEAM gave training to the Karisma Batik group to make fashion products made from Ngantang Agung typical batik. The stages of the community service program carried out in the Ngantang Agung batik village are surveys to partners, analysis, solving, training, output products, and evaluation. The sewing training activity was attended by 30 participants. This activity succeeded in making fashion products in the form of tunics and shirts of various sizes with batik materials in Sumberagung Village. All participants were considered very enthusiastic about participating in the training from start to finish and it is hoped that the participants will gain knowledge in the form of sewing skills which will become the provision for the development of the Karisma Agung batik team in the future. Keywords : training, skills, sewing, batik Abstrak Guna menjadikan batik menjadi pakaian jadi, kelompok batik karisma sangat membutuhkan pelatihan tentang bagaimana cara menjahit busana. Pelatihan menjahit ini sangat penting untuk membekali sumber daya manusia untuk terampil dalam membuat busana guna menjadikan batik yang tadinya berupa lembaran bahan sandang bisa menjadi bentuk busana jadi dan siap pakai. Keterbatasan sumberdaya manusia yang dimiliki untuk mengeksplor produk batik menginpirasi kami TIM PKM UM guna memberikan pelatihan kepada kelompok karisma batik untuk membuat produk busana berbahan batik khas ngantang agung. Tahapan dari program pengabdian masyarakat yang dilaksanakan di kampung batik ngantang agung adalah Survey ke mitra, menganalisa, pemecahan, pelatihan, produk luaran, dan evaluasi. Kegiatan pelatihan menjahit telah diikuti oleh 30 peserta. Kegiatan ini berhasil membuat produk busana berupa tunik dan kemeja berbagai ukuran dengan bahan batik di Desa Sumberagung. Seluruh peserta dinilai sangat antusias mengikuti pelatihan mulai dari awal hingga akhir dan diharapakan peserta mendapatkan ilmu berupa ketrampilan menjahit yang menjadi bekal pengembangan tim batik karisma agung di masa depan. Kata kunci : pelatihan, ketrampilan, menjahit, batik